Using Illustration Images to Enhance Junior High School Students’ Writing Skills - Katharina Barbe; Geminastiti Sakkir; Evi Syafitri; Syarifuddin Dollah (Naifaderu Cipta Sejahtera, 2023)
Purpose The purpose of this research is to explore the use of visual media illustration images in improving secondary school students' paragraph writing skills. Methodology This study used a pre-experimental one-group pretest-posttest design method. This research was conducted in one of the Indonesian public secondary schools. The population in this study were all students enrolling in the final year of their education. The researcher used a purposive random sampling technique due to the suitability of the purpose of the research. The instrument for the research is a written pre and post-tests Results/Findings Based on the results of the study, it is clear that the use of visual illustration media can improve students' paragraph writing skills, with the mean posttest is greater than the mean of pretest (57.08, 73.36). The significance value of this research is <000, which means it is smaller than the significance level of 0.05. The results of the pretest and post-tests obtained t-table 2.063, t-count 12.629, df 24, and p<000. From this data, it indicates that the use of visual media illustration images can improve students' paragraph writing skills. Implications The evidence from the research shows that the use of visual media illustration images can have pedagogical impact on teaching writing including the improvement of the understanding of paragraph writing components. This media can be an alternative tool for educators for teaching paragraph writing.